Professores de língua portuguesa : uma análise das concepções de formação contínua que norteiam os processos de desenvolvimento profissional na escola - Monteiro, Renata Ribeiro (2015)
This study is the result of a master research developed jointly to the Pos-Graduate Program in Education of the Federal University of Mato Grosso, Rondonópolis college city (PPGEDU / UFMT / CUR). It is included in Teacher Training and Educational Public Policy branch. It assumes as its premise that the way in which the subject conceives to be continuous training implies both on the process of developing projects and training programs as on the subject's performance in this process. Based on it, we consider relevant searching further state of Mato Grosso pubic network Portuguese teacher’s conception continuated education. It involves the different segments intertwined in this formative web, be they Portuguese teachers; pedagogical coordinator; former teacher, representative of the Center for Training and Maintenance of Basic Education Professionals (CEFAPRO); pedagogical advisor and head of training for professionals of Education basically SEDUC. Based on qualitative approach, research process followed the steps of Content Analysis, recommended by Laurence Bardin. As data collection instruments, it used questionnaires (fro subjects characterizing), interviews and document analysis. Employees subjects are longlife job portuguese language teachers on state system, englobing ten teachers from all those different segments alread mentioned. Thus, supported on Content Analysis theoretical framework as research method, analysis arise from confronting interviews individually colected with the legal documents that regulate continuated education in the state of Mato Grosso. Going through such steps, this study sought answering the following questions: do the policies of continuated education are in line with teachers’ needs and desire? Structure and organization of the Educator's room Project as continuated education policy have allowed effective teachers participation? What views on continuing education do Portuguese Language teachers hold about continuated education programs in which they have participated? Research presents data which reflect continuated education relevance as a means of personal and professional growth. It gets clear since educators pointed out that, for the exercise of their function, they must continually constructing their formation. Yet, according to them, it aims at improving their knowledge, skills and methodological techniques can help them in the teaching practice challenges. However, we found that still prevails a pragmatic view on continuated education because it is characterized as upgrade, improvement and training processes. In general, teachers assert that training has low contribution to their teaching practices. In justification for such fact, the subjects pointed it out: discussions focused on more general topics; discontinuity in themes addressed; lack of training in the specific area of performance and also overload work, making it difficult to participate in studies dating. In summary, this study showed that there is still no consonance between the concepts of portuguese-speaking professionals and which Mato Grosso State Training Policy stipulates as training proposals for this segment.